Short- and Long-Term Determinants of Residential Electricity Demand in Turkey - TatlÄ±, Halim (International Journal of Economics, Management and Accounting, 2017)
The purpose of this study is to predict the factors affecting the residential electricity demand by using a multivariate econometric model. The variables of the model established in this context are net electricity consumption in the residential sector, the price of electricity, real income per capita, average air temperature showing the climatic conditions and the urbanization rate. Residential electricity demand was analyzed for short- and long-term with the ARDL-Bound Testing by using the annual data for the years 1990-2014 in Turkey. As a result of the analyses both short- and long-term residential electricity demand was found to be negatively and significantly affected by price of electricity and positively and significantly affected by income, average temperature and urbanization rate. The price elasticity of demand was estimated to be smaller than 1 in both short- and long-term. Although income elasticity of demand was estimated to be smaller than 1 in the short-term, income elasticity of demand was found to be higher than 1 in the long-term. In addition, climatic condition was found to be most effective variable affecting residential electricity demand.